Allocation, allocation, allocation! The political economy of the development of the European Union Emissions Trading System. (1st August 2022) - Sato, Misato; Rafaty, Ryan; Calel, Raphael; Grubb, Michael
Abstract: The European Union's pioneering carbon Emissions Trading System, the EU ETS, has inspired countries around the world to launch their own CO2 markets. This paper analyses the evolution of the EU ETS from a political economy perspective, emphasizing the interaction of economic principles and political interests at pivotal moments, and showing how each compromise changed the scope for future design choices. We focus on the allowance allocation issue, which provides a window into the complex tug‐of‐war between economic efficiency and the politics of distribution. Our account highlights the dynamic nature of CO2 market reform, and provides lessons that can help inform the design of more stable and effective CO2 markets in the future. This article is categorized under: Climate Economics > Economics of Mitigation The Carbon Economy and Climate Mitigation > Policies, Instruments, Lifestyles, Behavior EU ETS futures prices and key events: Source : European Energy Exchange (EEX) and EEA for EUA Futures 2007. ICAP Allowance Price Explorer and Ember for EUA Futures series.